The human scale - Wright, Lawrence, 1947- (Alfred A. Knopf, 2025)
"Tony Malik is a half-Irish, half-Arab New York based FBI agent, specializing in money flowing from drug and arms deals. The novel opens in shocking fashion, with Malik seriously injured by a terrorist-planted bomb. During his lengthy recuperative process, his life changes radically. A long-term relationship ends, and his job is on the verge of being taken away from him. During this period he learns more about his roots and becomes interested in his father's past and family -- his father came to America years ago from Palestine. He decides to make a trip to his father's homeland to attend the wedding of his niece, whom he has never met. As a result of his plans, he is given a simple assignment by his boss at the FBI, partly to see how well he can still do his job. That simple assignment becomes extremely complicated. As soon as he arrives in Gaza, the Israeli police chief overseeing the area is murdered. Malik is at first a suspect. Then, due to his superior investigative skills, he is invited into the Israeli investigation, seeking the murderer. At the center of this novel is Malik's relationship with Yossi, the hardline anti-Arab Israeli police officer leading the investigation. They must learn to trust each other because, as they move closer to solving the case, they realize there is no one else they can trust on either side. Extraordinary three dimensional characters populate this novel: Yossi's daughter, studying in Paris, trying to escape the violence that surrounds her in Israel; Malik's niece, whose wedding and life are shattered by the murder; her fiancé, a peacenik whose existence is complicated by the fact that his cousin is high up in the Hamas command; religious leaders on both sides; corrupt Israeli cops; Palestinians thirsting for violence against Israel; Israelis determined to crush the Palestinians. Lawrence Wright brings a wide and complicated tapestry to life, one that culminates on October 7 with the deadly Hamas attack on Israel. But he has written more than just a thriller, or even just an examination of all these complicated lives. He has written a novel that manages to explore and explain much of the devastating history that encompasses the relationship between Israel and Palestine--and shows it to us in a way that poignantly reveals the tragic human scale that is involved"--